Literature Review of the Stigma of People Experiencing Homelessness - Laitres, Karina (MacEwan University Student eJournal, 2024)
I live in a community with a large homeless population. I witness and take part in conversations with community members and have noted that a seemingly large portion of them have little empathy, education, or understanding of what it means to be homeless. These conversations are often very polarizing, as there are many stigmas regarding the homeless population. I am passionate about promoting change. I want to educate the community, to help them understand and have empathy. In my attempt to decrease the stigmas that homeless people face, I have completed a literature review to research what these stigmas are and how to address them effectively. I aim to find ways to most effectively educate my community on homelessness.